Pengaruh Sosialisasi PMK 81/2024 dan Modernisasi Coretax terhadap Kepatuhan Wajib Pajak UMKM di Tabanan - I Putu Gde Chandra Artha Aryasa; Cok Istri Ratna Sari Dewi (Jurnal Proaksi, 2025)
Main Purpose - analyzing the factors that influence taxpayer compliance of small, micro, and medium enterprises (MSMEs) at the Tabanan Tax Office.Method - The study employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) for data analysis. The population in this research consists of MSME actors registered as individual taxpayers at the Tabanan Pratama Tax Office. The sampling technique utilized is non-probability sampling with incidental and purposive sampling approaches.Main Findings - The study reveals that MSME taxpayers’ compliance in Tabanan can be improved by providing knowledge through the socialization of PMK 81/2024 and the transition to a better system (Coretax). However, the effectiveness depends on the clarity of information and the technical support provided by tax authorities. This phenomenon indicates that education and administrative modernization are more dominant in shaping positive attitudes and compliance intentions compared to cognitive factors alone, while  low tax literacy and knowledge did not affect taxpayer compliance in this study.Theory and Practical Implications - The findings reinforce the Theory of Planned Behavior (Ajzen, 1991)  by demonstrating that perceived behavioral control through system modernization (Coretax) and the development of positive attitudes through the socialization of PMK 81/2024 are more dominant than cognitive factors in driving MSME compliance (Cipta & Ginting, 2025; Sunaryo, 2024). The results imply that the Directorate General of Taxes needs to expand community-based socialization programs and accelerate the implementation of Coretax with user-friendly guidelines to create a more effective tax compliance ecosystem for MSMEs.Novelty -  This study offers novelty by examining the impact of the socialization of PMK 81/2024 and the modernization of the Coretax system, which has just been introduced by the Indonesian government in 2025.